Strategi Bisnis Digital dengan Pemasaran Digital yang Efektif dalam Meningkatkan Daya Saing Perusahaan dan Inovasi Berkelanjutan - Renni Mayasari; Abul Khair, Ahmad; Muhammad Nur Madani (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
In an increasingly competitive digital era, digital business strategies with digital marketing are key to increasing company competitiveness and sustainable innovation. Companies must be able to utilize digital platforms and media effectively to reach a wider range of consumers and build closer relationships with consumers. This study aims to identify digital business strategies with digital marketing that are effective in increasing company competitiveness and sustainable innovation. This study uses a literature review method to collect and analyze various literature related to effective digital marketing strategies. Digital marketing has become a key element in digital business strategies, namely by: 1. Utilizing digital platforms and media, 2. collaborating with other companies and influencers to reach consumers effectively, 3. Dividing digital marketing based on the type of social media, 4. Creating digital content, 5. Analyzing consumer data with AI and Machine Learning, 6. Optimizing the company's website. By understanding the latest trends and technologies in digital marketing, companies can develop strategies that are more focused and responsive to rapid changes in the business environment. Overall, this study shows that digital business strategies with effective digital marketing in increasing competitiveness and sustainable innovation can provide significant results for companies in the digital era.